Oviposition Preference and Antibiosis to Spodoptera frugiperda (Lepidoptera: Noctuidae) in Brazilian Maize Landraces - Nogueira, Luciano [UNESP]; Costa, Eduardo Neves; Di Bello, Mirella Marconato [UNESP]; Diniz, Juno Ferreira Silva; Ribeiro, Zulene Antônio [UNESP]; Boiça Júnior, Arlindo Leal [UNESP] (Oxford University Press (OUP), 2019)
Spodoptera frugiperda (J.E. Smith) is a major pest of maize [Zea mays L. (Poales: Poaceae)] in tropical and subtropical regions. We aimed to evaluate the oviposition preference, growth, and survival of S. frugiperda on maize landraces and assess the nutritional quality of the leaves of different Brazilian maize landraces through evaluation of consumption indices. The oviposition preference was assayed using free and no-choice tests, and antibiosis by evaluating insect growth parameters, including weight, development time, survival in different stages of the life cycle, and nutritional indices. Landrace Pérola and cultivar BRS-Caatingueiro were the least preferred for S. frugiperda oviposition. Larvae fed with landrace Pérola consumed a lower amount of leaves and showed longer development time and lower survival until the end of the pupal stage. Larvae fed with the leaves of landrace Pérola and cultivar BRS-Caatingueiro displayed the lowest nutritional indices. Overall, Pérola was the most promising source of resistance to S. frugiperda. Identification of resistance in maize landraces may support breeding programs aimed at developing cultivars and hybrids resistant to S. frugiperda and other agricultural pests and inform growers regarding resistance of their landraces for integrated pest management.
Keywords: antixenosis; fall armyworm; host plant resistance to insect; native resistance; Zea mays